2015
DOI: 10.1016/j.celrep.2015.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and Diversity of the Mammalian Sialome Revealed by Nidovirus Virolectins

Abstract: SUMMARY Sialic acids (Sias), 9-carbon-backbone sugars, are among the most complex and versatile molecules of life. As terminal residues of glycans on proteins and lipids, Sias are key elements of glycotopes of both cellular and microbial lectins and thus act as important molecular tags in cell recognition and signaling events. Their functions in such interactions can be regulated by post-synthetic modifications, the most common of which is differential Sia-O-acetylation (O-Ac-Sias). The biology of O-Ac-Sias re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(128 citation statements)
references
References 50 publications
3
124
0
Order By: Relevance
“…Only a single study showed that the ability of NA to bind red blood cells corresponded to the cleavage efficiencies of other multivalent substrates (26). Enhancement of catalytic efficiency resulting from catalytic and carbohydrate-binding domains interacting simultaneously with a polyvalent substrate appears to be a general feature of most glycoside hydrolases, as most of these enzymes have been shown to contain lectin domains, including eukaryotic and bacterial NA proteins (44), as well as other viral-receptordestroying enzymes (45,46). The 2nd SIA-binding site, which is adjacent to the actual NA active site, may enhance the catalytic efficiency of NA by recruiting and keeping multivalent sialosides close to the active site (26,43).…”
Section: Discussionmentioning
confidence: 99%
“…Only a single study showed that the ability of NA to bind red blood cells corresponded to the cleavage efficiencies of other multivalent substrates (26). Enhancement of catalytic efficiency resulting from catalytic and carbohydrate-binding domains interacting simultaneously with a polyvalent substrate appears to be a general feature of most glycoside hydrolases, as most of these enzymes have been shown to contain lectin domains, including eukaryotic and bacterial NA proteins (44), as well as other viral-receptordestroying enzymes (45,46). The 2nd SIA-binding site, which is adjacent to the actual NA active site, may enhance the catalytic efficiency of NA by recruiting and keeping multivalent sialosides close to the active site (26,43).…”
Section: Discussionmentioning
confidence: 99%
“…Many sialylated glycans are synthesized in and presented on vertebrate cells, but detailed information about how those are produced and displayed is often lacking; however, it is clear that the relative display patterns of each modified Sia form can vary widely between even closely related animal species, as well as between and within different tissue types [26,27]. For example, 4-O-acetyl Sia (4-O-Ac) appears to be restricted to only a few tissue types in mice, including the colon, spleen, stomach, thymus, and uterus [27,28]. One factor determining the speciesspecific display of modified Sia is the presence and expression of the necessary enzymesas some vertebrate lineages may lack the intact genes encoding certain Sia-modifying enzymes.…”
Section: Sias: Modifications and Variationmentioning
confidence: 99%
“…It has been suggested that the loss of Neu5Gc in humans following divergence from our common ancestor with chimpanzees may have been beneficial by allowing resistance to Neu5Gc-specific pathogens, such as ancestral strains of Plasmodium malaria [34]. Another interesting case is the high variability of 4-O-Ac in many mammals, including apparent low levels or loss of that Sia form in cows, pigs, sheep, goats, and humans [26,27]. Again, the biological reasons for the highly variable synthesis and distribution of modified Sias are not known.…”
Section: Sias: Modifications and Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Key facets of glycan sialylation are now understood in considerable depth (e.g., as outlined in Figure 2), for instance the “sialome” (i.e., the collective complement of all sialic acids [59]) displayed on a cancer cell represents as many as 10 10 residues per cell [60, 61] but although important aspects of the complexity and diversity of the sialome are now understood at a rudimentary level [62], many questions remain. For example, to date there are no unifying sialylation signatures across different types of breast cancer cells for diagnostic use; in particular “glycosite” profiles (an example of this method is provided for pancreatic cancer cells [43, 44]) that could be used to distinguish different stages of breast cancer remain lacking.…”
Section: Glycosylation In Breast Cancermentioning
confidence: 99%